2009
DOI: 10.1111/j.1939-1676.2009.0354.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Guided Cytology of Spleen and Liver: A Prognostic Tool in Canine Cutaneous Mast Cell Tumor

Abstract: Background: In the clinical staging of cutaneous mast cell tumors (cMCT), the diagnosis of metastasis is controversial based on cytological examination of lymph nodes, spleen, liver, bone marrow, and blood.Objectives: To define the prognostic role of ultrasound-guided cytology of spleen and liver in cMCT. The results of cytological evaluation were compared in relation with survival time.Animals: Fifty-two client-owned dogs with a diagnosis of cMCT. Methods: Selection of cases was based on cytological evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 36 publications
8
91
1
2
Order By: Relevance
“…Initial staging included history and physical examination, complete blood cell count with differential, serum biochemistry, coagulation profile, cytological evaluation of the cutaneous nodule and regional lymph node, thoracic radiographs (3 views), abdominal ultrasound, fine‐needle aspirates of liver and spleen regardless of their sonographic appearance, and cytologic examination of bone marrow obtained from the iliac crest. Lymph nodes or viscera were considered metastatic, if mast cells appeared in clusters or sheets, in very large numbers or atypical on morphology, as previously documented 18. Histologically, nodal metastatic spread was supported by the localization of mast cells in the subcapsular sinuses; special histochemical stains (Giemsa) were used to detect poorly granulated mast cells.…”
Section: Methodsmentioning
confidence: 99%
“…Initial staging included history and physical examination, complete blood cell count with differential, serum biochemistry, coagulation profile, cytological evaluation of the cutaneous nodule and regional lymph node, thoracic radiographs (3 views), abdominal ultrasound, fine‐needle aspirates of liver and spleen regardless of their sonographic appearance, and cytologic examination of bone marrow obtained from the iliac crest. Lymph nodes or viscera were considered metastatic, if mast cells appeared in clusters or sheets, in very large numbers or atypical on morphology, as previously documented 18. Histologically, nodal metastatic spread was supported by the localization of mast cells in the subcapsular sinuses; special histochemical stains (Giemsa) were used to detect poorly granulated mast cells.…”
Section: Methodsmentioning
confidence: 99%
“…Where evidence of higher grade tumours exists, or there is evidence of MCT metastasis to the local lymph node, further staging to include abdominal ultrasound and possibly FNA of the liver and spleen is indicated. The latter is yet another debatable subject within veterinary oncology; some suggest that aspiration of even ultrasonographically normal livers and spleens should be performed owing to a poorer prognosis in dogs with mast cells detected at these sites (Stefanello and others 2009), while other studies have shown no value to aspirating normal appearing visceral organs (Finora and others 2006). The authors' approach is to aspirate the liver and/or spleen only where ultrasonographic changes are present or the tumour is considered high risk, with nodal metastasis detected.…”
Section: Diagnosismentioning
confidence: 99%
“…Primary hepatic neoplasias are hepatocellular adenoma and carcinoma; bile duct adenoma (cystadenoma) and carcinoma Continued such as nodular hyperplasia, pyogranulomatous hepatitis, chronic active hepatitis, and cirrhosis may also produce target lesions. [100][101][102] The liver may appear normal because there is an inherent difficulty in detecting mild changes in hepatic size and echogenicity. Hepatic lymphosarcomas have a variety of ultrasound appearances.…”
Section: Neoplasiamentioning
confidence: 99%